(untitled) (Journal of the College of Basic Education, 2026)
During World War I (1914–1918), the Ottoman Empire experienced a profound economic crisis that affected all its production and service sectors. The state’s participation in the war depleted its limited resources and deteriorated the agricultural, industrial, and commercial infrastructure, which was already weak before the outbreak of the war. Agriculture was directly affected by the recruitment of large numbers of peasants and the confiscation of livestock and agricultural equipment for the war effort, which led to a sharp decline in grain and cotton production and the outbreak of famines in some provinces, such as Syria and Iraq. The industrial sector declined sharply as a result of the interruption of raw materials from Europe, and many small workshops and factories ceased operations, with the exception of some military industries that were established with German support to meet the needs of the fronts. Regarding trade and public finances, the naval blockade imposed by the Allied powers caused an almost complete paralysis of exports and imports, and customs revenues declined significantly. Meanwhile, the Ottoman government resorted to printing money without cover, which led to severe monetary inflation and the loss of the value of the Ottoman lira. As a result, by the end of the war, the Ottoman Empire entered a state of comprehensive economic collapse, which represented one of the factors The main reason for its disintegration and fall in 1918, leaving a difficult economic and social legacy in its former areas of influence.